Method for preparing high-strength aluminum alloy containing rare earth elements using powder injection molding technology

Through the Al-Zn-Mg-Cu-Zr-Sn-RE aluminum alloy system, rare earth elements are used to react with oxide films to form dispersed oxides, and the binder and sintering system are optimized to solve the problems of oxide film removal and densification of injection-molded aluminum alloys, thereby achieving high-strength and high-efficiency production of small and complex-shaped parts.

CN115647365BActive Publication Date: 2025-09-26UNIV OF SCI & TECH BEIJING
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202211310469.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-10-25
Publication Date
2025-09-26
Estimated Expiration
2042-10-25

AI Technical Summary

Technical Problem

The existing injection molding aluminum alloy technology has problems such as difficulty in removing the oxide film, difficulty in removing the binder, and difficulty in controlling the liquid phase volume when preparing Al-Zn-Mg-Cu alloys, resulting in insufficient mechanical properties and difficulty in meeting high strength requirements.

Method used

The Al-Zn-Mg-Cu-Zr-Sn-RE aluminum alloy system is adopted. By adding rare earth elements Sc, Y or Er, their reaction with the oxide film forms dispersed oxides, and the binder and sintering system are optimized to achieve densified sintering.

Benefits of technology

The mechanical properties of aluminum alloy are improved, with the density reaching 98.1% and the tensile strength reaching 565MPa, making it suitable for efficient mass production of small and complex-shaped parts.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115647365B_ABST
    Figure CN115647365B_ABST
Patent Text Reader

Abstract

A method for preparing a high-strength aluminum alloy containing rare earth elements using powder injection molding technology belongs to the field of powder injection molding. The present invention mixes the raw material powders in a certain proportion, adds a wax-based binder suitable for the aluminum alloy injection molding process, prepares an aluminum alloy green body by injection molding, and after solvent degreasing and thermal degreasing, performs sintering and heat treatment processes to obtain aluminum alloy parts. By optimizing the sintering system and heat treatment system, etc., the microstructure is regulated to improve the mechanical properties of the aluminum alloy. Elements such as RE, Zr, and Sn are added, and rare earth elements are used to break the semi-continuous oxide layer at the grain boundary and to produce dispersion strengthening and second phase strengthening during the heat treatment of the injection-molded aluminum alloy, thereby improving the mechanical properties of the injection-molded aluminum alloy. The aluminum alloy material prepared by the present invention has a uniform microstructure, excellent mechanical properties, a density of 98.1%, and a tensile strength of 565 MPa after heat treatment. It can be used to prepare high-performance and complex-shaped aluminum alloy parts in large quantities at low cost.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention provides a method for preparing a high-strength aluminum alloy containing rare earth elements by utilizing a powder injection molding technology, and belongs to the field of powder metallurgy. Background Art

[0002] In recent years, with the increasing demand for lightweight, high-strength, small, complex-shaped structural parts in sectors such as automotive, consumer electronics, 5G communications, wearable devices, and industrial robotics, the use of high-strength aluminum alloys to replace traditional iron-based materials has become a key approach to achieving lightweighting. As a lightweight, high-strength material, aluminum alloys are used in transportation, aerospace, marine, construction, and electronics. They are particularly important for lightweight components in the automotive, aircraft, aerospace, and shipbuilding industries. Machining and 3D printing methods for producing small, complex-shaped aluminum alloy parts present challenges such as high cost and inadequate mass production. Casting methods inevitably lead to compositional segregation in aluminum alloy production. Powder pressing and sintering processes are often limited by mold geometry and can be prone to issues with product microstructure. Metal injection molding (MIM) is a new component manufacturing technology developed by successfully integrating plastic injection molding technology into powder metallurgy. It is a near-net-shape process suitable for producing special-shaped parts, offering low cost and high-volume production. It offers unique advantages for producing small, complex-shaped parts.

[0003] The application of powder injection molding technology to the preparation of aluminum alloy parts faces the following challenges: ① Compared with the traditional press-sintering powder metallurgy process, the aluminum powder and other raw material powders for injection molding aluminum alloys have a high oxygen content (2000-5000ppm). The alloy powder has not undergone plastic deformation, and the surface oxide film is more complete. During the feeding preparation process and degreasing process, the alloy powder will react with oxygen and water in the air and binder, increasing the thickness of the oxide film on the powder surface and increasing the difficulty of sintering and densifying the aluminum alloy powder. ② Compared with the traditional press-sintering powder metallurgy process, the injection molded blank contains 30-40vol.% binder. After the binder is removed, a large number of pores remain, making sintering by diffusion between particles more difficult. ③ The alloying elements added to the injection molded aluminum alloy will form a certain amount of liquid phase within the degreasing temperature range and above the degreasing temperature, which will have adverse effects on the degreasing process and densification sintering after the binder is completely removed, such as degreasing difficulties and easy deformation.

[0004] At present, there are few studies on injection molding of aluminum alloys, and only a few literatures and patents report on aluminum alloy injection molding technology. Acar et al. used gas atomized pure aluminum powder with a medium particle size of D 50The sample was 7.35 μm in diameter and sintered in a high-purity nitrogen environment at 650°C for 60 min. The maximum density, maximum tensile strength, and maximum hardness of the sample were 96.2%, 126 MPa, and 46 HB, respectively. [Acar L, Gulsoy HO. Sintering parameters and mechanical properties of injection molded aluminum powder [J]. Powder Metallurgy. 2011, 54(3): 427-431.] Schaffer et al. used AA6061 (Al-0.95Mg-0.65Si-0.27Cu) alloy powder and Sn powder as raw material powders, promoted sintering by adding Sn element, and finally prepared aluminum alloy samples by injection molding when 2wt.% Sn was added. The sintered density could reach 97%, the tensile strength was 165MPa, and the strength after artificial aging could reach 300MPa [Liu ZY, Sercombe TB, Schaffer GB. Metal injection molding of aluminum alloy 6061 with tin [J]. Powder Metallurgy. 2008, 51(1): 78-83.]. Schaffer et al. also used AA6061 alloy powder, Sn powder and AlN powder as raw materials and prepared AlN fine particle reinforced aluminum matrix composite materials by powder injection molding. After sintering at 640℃ in a high-purity N2 environment for 2 hours, the sintered density reached 97%. After T4 heat treatment, the yield strength, tensile strength and elongation of the composite material are 120 MPa, 260 MPa and 8% respectively [Liu ZY, Kent D, Schaffer G B. Powder injection moulding of an Al-AlN metal matrix composite [J]. Materials Science & Engineering A, 2009, 513.]. Ni et al. used Al-Si pre-alloyed powder as raw material, used a binder composed of high-density polyethylene, palm oil wax and stearic acid, and sintered it in a high-purity N2 environment at 550 ° C for 3 hours. The density can reach 95.5%, the tensile strength is 154 MPa, and the hardness is 58 HBW [Ni J, Yu M, Han K. Debinding and Sintering of an Injection-Moulded Hypereutectic Al-Si Alloy [J]. Materials, 2018, 11 (5): 807.].Du Zhiyuan et al. used Al, Cu, Sn elemental powders and Al-50Mg, Al-12Si intermediate alloy powders as raw materials to prepare Al-4Cu-2Mg-0.8Si-0.5Sn. The density reached more than 98% under nitrogen sintering atmosphere, and the tensile strength reached 400 MPa after aging treatment [Du Zhiyuan, Wu Mao, Qiu Tingting, Qu Xuanhui. Injection molding of Al-Cu-Mg-Si aluminum alloys [J]. Journal of the Chinese Society for Nonferrous Metals, 2019, 29(11): 2471-2480.]. At the same time, China's invention patent "A method for preparing high-performance aluminum alloy using powder injection molding technology", application number: 201711182052.5, discloses an aluminum alloy injection molding technology based on the Al-Cu-Mg-Si system, wherein the mass percentage of the aluminum alloy components is: Cu 3-6%, Mg 1-3%, Si 0.2-2.0%, Sn 0.1-2.0%, and Al is the remainder of the alloy system. The tensile strength of the prepared aluminum alloy parts reaches 300MPa.

[0005] In summary, the research on injection molded aluminum alloys mainly focuses on pure Al, Al-Si system, Al-Cu-Mg-Si and other alloy systems. Due to the different material systems and types of reinforcing phases, the strength of injection molded aluminum alloy parts prepared by these systems is generally not high, and the mechanical properties are much lower than those of cast aluminum alloys with similar compositions. The performance is difficult to meet the current higher strength requirements, so it is necessary to learn from the composition of traditional 7 series high-strength aluminum alloys. However, the use of injection molding technology to prepare Al-Zn-Mg-Cu aluminum alloys has the following problems: ① The existing Al-Zn-Mg-Cu aluminum alloys are all based on the standard composition of cast and forged aluminum alloys, with poor sintering performance and are not suitable for aluminum alloy injection molding process; ② In Al-Zn-Mg-Cu alloys, the use of Mg element can break the surface of aluminum powder. ③ The Zn element has a high diffusion coefficient in Al and is volatile. The Al-Zn eutectic liquid phase formed during the sintering process is transient, and the content of other liquid phase-forming elements Cu is relatively small, making it difficult to control the amount of liquid phase in the Al-Zn-Mg-Cu system. ④ Since the densification of the green body is achieved by liquid phase filling during the sintering process of aluminum alloy, and the liquid phase formation temperature of Al-Zn alloy is relatively low (380℃), the traditional binder system is difficult to evaporate completely at this time, which has adverse effects on the degreasing process and the densification sintering after the binder is completely removed, such as degreasing difficulties and easy deformation, affecting the densification of the alloy. Summary of the Invention

[0006] The present invention provides a method for preparing a high-strength aluminum alloy containing rare earth elements by using powder injection molding technology, in particular a method for preparing an Al-Zn-Mg-Cu-Zr-Sn-RE (RE is Sc, Y or Er) series aluminum alloy by using powder injection molding technology. The present invention designs an Al-Zn-Mg-Cu-Zr-Sn-RE aluminum alloy system with good sintering characteristics and meeting the requirements of the injection molding process based on the liquid phase sintering principle. The Mg element is used to quickly break the oxide film on the surface of the Al powder and other raw material powder particles. The characteristics of rare earth elements such as high affinity with oxygen, strong reducing property and easy segregation at grain boundaries are utilized to make the rare earth elements react with oxide layers such as MgO and MgAl2O4 at the grain boundaries, so that the semi-continuous oxide layers at the grain boundaries are converted into fine and dispersed rare earth oxide particles, thereby strengthening the grain boundaries and improving the mechanical properties of the aluminum alloy. The densification sintering of the injection molded aluminum alloy is achieved by optimizing the binder system, the degreasing process and the sintering system. The morphology, size and distribution of the intracrystalline precipitated phase, the grain boundary precipitated phase and the grain boundary oxide are regulated by optimizing the sintering system and the heat treatment system, thereby improving the mechanical properties of the injection molded aluminum alloy.

[0007] A method for preparing an Al-Zn-Mg-Cu-Zr-Sn-RE series aluminum alloy using a powder injection molding technology is characterized by: taking an Al-Zn-Mg-Cu alloy system as a basis, adding a small amount of RE, Zr, and Sn elements; using pure Al powder as a main raw material, and introducing other alloying elements in the form of elemental powder or simple intermediate alloy powder; after uniformly mixing the raw material powders according to a certain proportion, adding a wax-based binder suitable for an aluminum alloy injection molding process, and placing the raw material powders on a roller mixer for mixing to obtain a feed, preparing a green body by injection molding technology, undergoing solvent degreasing, performing a thermal degreasing-sintering integrated step in a high-purity nitrogen atmosphere, and undergoing solid solution and aging treatment to obtain an injection-molded aluminum alloy product with high density and high mechanical properties.

[0008] Furthermore, the mass percentages of the alloying elements in the injection molding aluminum alloy are: Zn 4.5-7.5%, Mg 2.0-4.0%, Cu 1.5-3.5%, Sn 0.1-0.4%, RE 0.05-0.4%, Zr 0.025-0.2%, with Al as the balance. The preferred mass percentages of the alloying elements selected in the present invention are: Zn 5.5-7.0%, Mg 2.3-3.4%, Cu 1.8-2.7%, Sn 0.15-0.30%, RE 0.2-0.4%, Zr 0.1-0.2%, with Al as the balance.

[0009] Note: Compared to powder compaction sintering, injection molded aluminum alloys retain a large amount of pores after solvent debinding and thermal debinding, so more liquid phase must be generated during the sintering process to achieve densification. The liquid phase required to achieve densification in compaction sintered alloys is generally 20 vol.%. According to Thermo-Calc software, the liquid phase range for Al-Zn-Mg-Cu-Zr-Sn-RE aluminum alloys is 20-35 vol.%. Considering that injection molded blanks have a large amount of voids after debinding, the liquid phase in injection molded aluminum alloy systems should be maintained at around 30-40 vol.%.

[0010] In the alloy system of the present invention, Zn and Mg elements are the main strengthening elements in the system, and Zn and Cu elements are the main liquid phase forming elements in the system, which are used in the liquid phase assisted sintering process to complete the sintering densification of the aluminum alloy; Mg element is mainly used to form MgZn2 strengthening phase and break the oxide film on the surface of Al powder and other raw material powder particles. A part of Mg element is solid-dissolved in the aluminum matrix and forms MgZn2 strengthening phase during the aging process, thereby improving the strength of the alloy; a part of Mg element will diffuse to the grain boundary and react with the oxide film, quickly breaking the oxide film to form oxide layers such as MgO and MgAl2O4, and the content of Mg element is controlled at 2.0-4.0wt%; rare earth elements (Sc, Y and Er) have limited solid solubility in Al (such as the maximum solid solubility of Sc in Al is 0.38wt%), and a part of rare earth elements is solid-dissolved in the Al matrix and forms Al2RE and Al3RE particles dispersed and precipitated after aging treatment, which plays a dispersion strengthening role; the remaining rare earth elements tend to segregate at the grain boundary, and the rare earth elements tend to segregate at the grain boundary. Earth elements have strong reducing properties and great affinity with oxygen. They react with the oxide layer at the grain boundary, transforming the semi-continuous oxide layer at the grain boundary into fine, dispersed rare earth element oxides, thereby improving the mechanical properties of the aluminum alloy. Therefore, the content of rare earth elements (Sc, Y and Er) is controlled within the range of 0.05-0.4wt%; Zr atoms can occupy the lattice of the Al-RE precipitate phase and form a thin shell of the Al-RE-Zr ternary alloy phase around the core of the precipitate phase. This core-shell structure can reduce the misalignment between the Al-RE precipitate phase and the Al matrix. Matching and reducing interfacial energy can slow down the coarsening rate of the precipitate phase, reduce the size of the precipitate phase, and enhance the dispersion strengthening effect. The maximum solubility of Zr in the RE lattice of the precipitate phase is 50%, so the Zr content is controlled to 50% of the RE content; the trace alloying element Sn can reduce the surface tension of the liquid phase generated during the sintering process, making it easier for the alloy liquid phase to fill the pores. At the same time, the liquid phase Sn can spread on the surface of the Al particles, reduce the nitriding rate of the Al particles, improve the sintering performance, and promote the densification sintering of injection molded aluminum alloys.

[0011] Furthermore, the particle sizes of the raw material powders used for injection are respectively Al: 10-30 μm, Cu: 10-40 μm, Sn: 5-20 μm, Al-50Zn: 15-45 μm, Al-50Mg: 35-50 μm and Al-Mg-RE-Zr: 10-30 μm.

[0012] Note: With the exception of Al-Mg-Zr-RE powder, all raw materials are either elemental powders or binary alloy powders. This allows for tailoring the specific alloy composition to meet diverse performance requirements. Furthermore, the raw powders used are common commercial aluminum alloy powders, significantly reducing costs compared to custom multi-element aluminum alloy powders.

[0013] During the sintering process of Al-Zn-Mg-Cu aluminum alloys, some Mg will penetrate into the powder grain boundaries through solid-state diffusion and react with Al2O3 to form oxides such as MgO and MgAl2O4, thereby breaking down the oxide film and promoting liquid-phase sintering. However, the semi-continuous oxide layer formed by the reaction will reduce the mechanical properties of the aluminum alloy. By adding rare earth elements to the Al-Zn-Mg-Cu aluminum alloy, the rare earth elements react with Al2O3, MgO, and MgAl2O4, transforming the semi-continuous oxide layer at the grain boundaries into fine, dispersed rare earth oxide particles. However, since the diffusion coefficient of rare earth elements in Al is small and the solid-state diffusion is slow, the present invention chooses to add RE and Zr elements in the form of Al-Mg-Zr-RE alloy powder to improve the reaction efficiency of rare earth elements with grain boundary oxides such as Al2O3, MgO, and MgAl2O4. At the same time, rare earth elements are added in combination with Zr in the aluminum alloy. Zr atoms can replace part of the rare earth atoms in the Al-RE precipitated phase, forming a thin shell layer of Al-RE-Zr ternary alloy phase around the core of the precipitated phase. This core-shell structure can reduce the coarsening rate of the precipitated phase, reduce the size of the precipitated phase, and improve the dispersion strengthening effect.

[0014] Furthermore, the weight percentages of the components of the binder for injection molding aluminum alloy are: paraffin wax (33-66%), beeswax (0-33%), low-density polyethylene (0-20%), high-density polyethylene (0-20%), polypropylene (0-20%), and stearic acid (5-15%). The preferred binder components of the present invention are: paraffin wax (33-66%), high-density polyethylene (0-15%), polypropylene (10-20%), and stearic acid (8-12%).

[0015] Note: Because the eutectic temperatures of Al-Zn, Al-Mg, and Al-Cu in aluminum alloys are relatively low, at 380°C, 460°C, and 550°C, respectively, the binder of the present invention preferably uses paraffin wax, high-density polyethylene, polypropylene, and stearic acid, four binders with relatively low volatility temperatures, to reduce liquid phase formation during the degreasing process and hinder binder volatilization. Selecting binders with different volatility temperatures creates a degreasing temperature gradient during the degreasing process, which helps the aluminum alloy blank maintain its shape. Stearic acid also acts as a lubricant.

[0016] Furthermore, the loading amount of the aluminum alloy feed for injection molding is 58-66 vol.%, that is, the aluminum alloy powder in the feed accounts for 58-66% of the total volume; the mixing parameters are: mixing temperature 160-180° C., and mixing time 1.5-2.5 h.

[0017] Note: The mixing temperature and time will directly affect the quality of the feed. If the mixing temperature is too high, the binder will volatilize, causing the determined powder loading to deviate. If the mixing temperature is too low, the binder will not melt sufficiently to wet the powder. If the mixing time is too long, excessive shearing will occur, making the powder viscosity too high. If the mixing time is too short, the mixing will not be uniform.

[0018] Furthermore, the injection parameters of the aluminum alloy for injection molding are: injection temperature of 155-170°C, injection pressure of 170-180 bar, injection speed of 50-70%, and mold temperature of 40-60°C. Preferably, the injection parameters are: injection temperature of 160°C, injection pressure of 175 bar, injection speed of 65%, and mold temperature of 50°C.

[0019] Note: Injection temperature affects powder mobility and mold filling properties; appropriate injection pressure can squeeze out bubbles within the sample, reduce edge flash, and ensure surface finish; a reasonable injection speed can effectively improve the efficiency and quality of injection molding. The above injection molding process parameters can produce aluminum alloy green bodies with a complete, smooth surface and high strength.

[0020] Furthermore, the degreasing process of the aluminum alloy green body for injection molding is divided into two steps: solvent degreasing and thermal degreasing. The solvent for solvent degreasing is trichloroethylene, the temperature is 40-50°C, and the degreasing time is 9-15 hours. The preferred temperature is 45°C, and the preferred degreasing time is 10 hours.

[0021] Note: With the increase of degreasing temperature and the extension of degreasing time, the removal rate of soluble components of the binder (microcrystalline wax and stearic acid) is constantly increasing; however, the degreasing time at a specific temperature should not be too long, otherwise the solvent will diffuse into the injection blank, increasing the C content of the injection blank, which is not conducive to subsequent thermal degreasing and sintering; similarly, the degreasing temperature should not be too high, otherwise it will cause the injection blank to soften and deform; choosing to degreasing at 45°C for 9 to 11 hours, the degreasing rate of the injection blank is high and no obvious defects will be produced, which is conducive to the normal subsequent thermal degreasing and sintering.

[0022] Furthermore, the thermal degreasing and sintering process of the aluminum alloy for injection molding is completed in a one-step process, and the specific process parameters are: heating from room temperature to 150°C at 5°C / min; heating to 220-250°C at 0.5-2°C / min, and keeping warm for 90-180min; heating to 390-410°C at 0.5-2°C / min, and keeping warm for 180-240min; heating to 440- 460°C, hold for 120-180 minutes; increase the temperature to 470-480°C at a rate of 0.5-2°C / min and hold for 30-60 minutes; increase the temperature to 550-570°C at a rate of 1-10°C / min and hold for 30-60 minutes; increase the temperature to 610-620°C at a rate of 1-10°C / min and hold for 60-120 minutes; slowly cool to 200°C at a rate of 1-3°C / min and then cool with the furnace. High-purity nitrogen protection is used during both the thermal debinding process and the sintering process, with a nitrogen flow rate of 0.1-1mL / min.

[0023] Note: During the thermal debinding stage, a slower heating rate (0.5-2°C / min) should be used to prevent bubbling, cracking, and deformation of the debinded embryo. Maintaining the alloy within the temperature ranges of 220-250°C, 390-410°C, and 440-460°C ensures sufficient decomposition and volatilization of the binder. A faster heating rate during sintering can inhibit the diffusion of the liquid phase generated during sintering into the matrix, allowing the pores to be more fully filled with liquid and resulting in a denser structure. The temperature ranges of 450-470°C and 550-570°C correspond to the formation of the Al-Mg and Al-Cu eutectic liquid phases, respectively. Maintaining the alloy within these temperature ranges promotes the formation of liquid phases and densification of the sintered body. During cooling, a slower cooling rate can induce the precipitation of heterogeneous phases within the pores, significantly reducing porosity and achieving a higher density.

[0024] Furthermore, the solution treatment system of the aluminum alloy for injection molding is: heating to 450-480°C at a rate of 1-5°C / min, keeping warm for 1-8 hours, and water quenching.

[0025] Furthermore, the aging treatment system of the aluminum alloy for injection molding is: heating to 120-150°C at a rate of 1-5°C / min, and aging time is 2-24h.

[0026] The core concepts of this invention are: ① Designing an aluminum alloy composition that meets sintering requirements based on the principles of liquid-phase sintering; ② Selecting a binder with a volatilization temperature lower than the liquidus formation temperature of the Al-Zn alloy to prevent the formation of a liquidus phase during the degreasing process that would hinder binder volatilization. Selecting binders with different volatilization temperatures creates a degreasing temperature gradient during the degreasing process, which helps the aluminum alloy blank maintain its shape during the degreasing process. ③ Utilizing the differences in elemental diffusion rates, Mg rapidly breaks down oxide films, forming oxide layers such as MgO and MgAl2O4. Rare earth elements have limited solid solubility in aluminum. According to Humerothery's rule, they diffuse into grain boundaries and segregate there, forming metallic compounds such as Al2RE and Al3RE. Due to their strong affinity for oxygen, rare earth elements react with oxide films such as MgO and MgAl2O4 at the grain boundaries to form rare earth oxides (such as Sc2O3, Y2O3, and Er2O3). By regulating heat treatment, rare earth elements react with the grain boundary oxide layers, transforming the semi-continuous oxide films at the grain boundaries into fine, dispersed rare earth oxide particles, strengthening the grain boundaries and improving the mechanical properties of the aluminum alloy. ④ By optimizing the sintering and heat treatment regimes, densified sintering of injection-molded aluminum alloys is achieved, and the morphology, size, and distribution of intragranular and grain boundary precipitates and grain boundary oxides are regulated to improve the mechanical properties of the aluminum alloy.

[0027] Compared with the prior art, the present invention has the following beneficial effects:

[0028] 1. The present invention successfully applies injection molding technology to the preparation of Al-Zn-Mg-Cu-Zr-Sn-RE series aluminum alloys and realizes densification sintering. Compared with the traditional Al-Zn-Mg-Cu series aluminum alloy preparation method, the injection molding method has the characteristics of high production efficiency, high material utilization rate, uniform composition distribution, and no need for subsequent processing. It has unique advantages in the batch preparation of small and complex-shaped aluminum alloy parts.

[0029] 2. Compared with the traditional Al-Zn-Mg-Cu series aluminum alloy composition, the aluminum alloy composition of the present invention adds elements such as RE, Zr, and Sn. Rare earth elements are used to break the semi-continuous oxide layer at the grain boundary, and rare earth elements produce dispersion strengthening and second phase strengthening during the heat treatment process of injection-molded aluminum alloy, thereby improving the mechanical properties of the injection-molded aluminum alloy. The prepared Al-Zn-Mg-Cu-Zr-Sn-RE series injection-molded aluminum alloy has excellent mechanical properties.

[0030] 3. The aluminum alloy material prepared by the method of the present invention has a uniform microstructure and a density of up to 98.1%. After heat treatment, the tensile strength can reach 565 MPa, which can realize the low-cost and large-scale production of high-performance complex-shaped aluminum alloy parts. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Attachment Figure 1 Microstructure morphology of injection molded aluminum alloy after sintering;

[0032] Attachment Figure 2 Microstructure of injection molded aluminum alloy after solution treatment.

[0033] (a) Micromorphology of grain boundaries in Al-Mg-Zn-Cu aluminum alloys;

[0034] (b) Microstructure of grain boundaries of Al-Zn-Mg-Cu-Zr-Sn-RE aluminum alloy with rare earth elements added. DETAILED DESCRIPTION

[0035] Example 1: Composition Optimization of Injection Molded Al-Zn-Mg-Cu-Zr-Sn-RE Aluminum Alloy System

[0036] a. Composition Design: The liquidus volume of this alloy system needs to be maintained at 30-40 vol%. Using Thermo-Calc software, the alloy composition was selected within the 30-40 vol% liquidus line. The Al, Zn, Mg, Cu, and Sn content were 8.5 wt%, 4.5-7.5 wt%, 2.0-4.0 wt%, 1.5-3.0 wt%, and 0.1-0.4 wt%, respectively. The effects of varying rare earth element (Sc, Y, and Er) content on the microstructure and properties of the injection molded aluminum alloy were investigated, with the selected content being 0.05 wt%, 0.1 wt%, 0.2 wt%, 0.3 wt%, and 0.4 wt%. The Zr content varied according to the rare earth element (Sc, Y, and Er) content, with the content varying from 0.025 wt%, 0.05 wt%, 0.1 wt%, 0.15 wt%, 0.2 wt%, and 0.25 wt%. According to the experimental results, the optimal contents of RE and Zr were determined, and the contents of Zn, Mg, Cu and Sn elements were regulated to determine the optimal contents of Zn, Mg, Cu and Sn elements.

[0037] b. Feed Preparation: Dry-blend the alloy powders according to the component ratio in a mixer for 2 hours to prepare a premixed powder. A wax-based binder is used, with the components weighed in a mass ratio of paraffin wax: high-density polyethylene: stearic acid: polypropylene = 57:9:11:14. The powder and binder are measured with an accuracy of 0.01g. The uniformly mixed powder and the prepared binder are weighed to a powder loading of 62 vol.%, and mixed in a CF-1L high-pressure internal mixer according to the procedure. The mixing temperature is 165°C. After 2 hours, the mixture becomes molten, is thoroughly mixed, and then removed and cooled.

[0038] c. Injection molding: After crushing the feed material, pour it into the barrel of the EM120-SVP / 2 injection molding machine and perform the injection operation. The injection temperature is 160℃, the injection pressure is 175bar, and the mold temperature is 50℃.

[0039] d. Debinding-sintering: trichloroethylene is used for solvent debinding, the debinding temperature is 45℃, and the debinding time is 10h; high-purity nitrogen is used as the atmosphere for thermal debinding and sintering, and the thermal debinding heating system is as follows: heating from room temperature to 150℃ at 5℃ / min; heating to 240℃ at 1℃ / min, keeping warm for 120min; heating to 400℃ at 1℃ / min, keeping warm for 180min; heating to 450℃ at 1℃ / min, keeping warm for 120min; heating to 480℃ at a rate of 1℃ / min, keeping warm for 60min; heating to 560℃ at 10℃ / min, keeping warm for 60min; heating to 620℃ at 10℃ / min, keeping warm for 60min; slowly cooling to 200℃ at 2℃ / min and then cooling with the furnace.

[0040] e. Heat treatment: The sintered samples were solution treated in a N2 atmosphere with the following process parameters: heating to 480°C at a rate of 1°C / min and holding at that temperature for 4 hours before water quenching. The solution treated samples were placed in a vacuum drying oven for peak aging treatment with the following process parameters: heating to 120°C at a rate of 5°C / min and holding at that temperature for 24 hours.

[0041] Table 1. Density and tensile strength of aluminum alloys with different compositions after sintering

[0042]

[0043]

[0044] By comparing the experimental results in Table 1, it can be seen that as the Zn content of the Al-Zn-Mg-Cu-RE-Zr-Sn aluminum alloy increases and the Mg, Cu, and Sn contents decrease, the yield strength and tensile strength of the aluminum alloy first increase and then decrease. This is because when the Mg, Cu, and Sn contents are high, more Al-Zn-Mg-Cu phases and Sn-rich phases remain at the grain boundaries after sintering and heat treatment, resulting in poor grain boundary bonding and poor mechanical properties. When the Zn:Mg ratio increases between 5:2 and 7:1, η'(MgZn) and η(MgZn2) become the primary strengthening phases in the aluminum alloy, improving its mechanical properties through precipitation strengthening. With increasing RE and Zr content, the yield strength and tensile strength of the aluminum alloy first increase and then decrease. This is because RE and Zr transform the semi-continuous oxide layer at the grain boundaries into fine, dispersed RE oxide particles, strengthening the grain boundaries and improving the mechanical properties of the aluminum alloy. However, increasing RE content forms coarse second-phase particles that segregate at the grain boundaries, reducing the bonding strength between the aluminum alloy grains and leading to a decrease in mechanical properties. Aluminum alloys with a mass percentage of the following elements: Zn 5.5-7.0%, Mg 2.3-3.4%, Cu 1.8-2.7%, Sn 0.15-0.30%, RE 0.2-0.4%, and Zr 0.1-0.2% exhibit higher mechanical properties. The optimized aluminum alloy has a maximum density of 98.1% after sintering, a yield strength of 517 MPa, and a tensile strength of 565 MPa.

[0045] Example 2: Optimization of the binder system for injection molded Al-Zn-Mg-Cu-Zr-Sn-RE aluminum alloy

[0046] a. Feedstock Preparation: Prepare the Al-Zn-Mg-Cu-Zr-Sn-RE elements in a mass ratio of 88.5:6.5:2.7:2.1:0.15:0.2:0.3 and dry-blend them in a mixer for 2 hours to prepare a premixed powder. A wax-based binder is used as the binder. The components are weighed according to the mass percentages in Table 2. The powder and binder are measured with an accuracy of 0.01g. The uniformly mixed powder and the prepared binder are weighed to a powder loading of 65 vol.%, and mixed in a CF-1L high-pressure internal mixer according to the following steps. The mixing temperature is 165°C. After 2 hours, the mixture becomes molten. After thorough mixing, remove and cool.

[0047] b. Injection Molding: The feed material was crushed and poured into the barrel of an EM120-SVP / 2 injection molding machine. The injection process was compared to determine the effects of different binder ratios on the injection process, as well as the integrity, finish, and strength of the resulting green parts. The injection temperature was 160°C, the injection pressure was 175 bar, and the mold temperature was 50°C.

[0048] c. Debinding-Sintering: Solvent debinding was performed using trichloroethylene at a debinding temperature of 45°C for 10 hours. High-purity nitrogen was used for thermal debinding and sintering. The thermal debinding heating schedule was as follows: room temperature to 150°C at 5°C / min; then to 240°C at 1°C / min, holding for 120 minutes; then to 400°C at 1°C / min, holding for 180 minutes; then to 450°C at 1°C / min, holding for 120 minutes; then to 480°C at 1°C / min, holding for 60 minutes; then to 560°C at 10°C / min, holding for 60 minutes; then to 620°C at 10°C / min, holding for 60 minutes; and finally, cooling slowly to 200°C at 2°C / min and then cooling in the furnace. The surface finish, strength, and degree of deformation of the aluminum alloy samples sintered with different binder ratios were compared.

[0049] Table 2. Effects of different binder systems on debinding and sintering performance

[0050]

[0051]

[0052] Through experimental comparison, it is found that the preferred binder composition by mass percentage is: paraffin: 58-64%, stearic acid 8-12%, high-density polyethylene 10-15%, and polypropylene 10-15%.

[0053] Example 3: Optimization of the heat treatment process for injection molded Al-Zn-Mg-Cu-Zr-Sn-RE aluminum alloy

[0054] a. Feedstock Preparation: Prepare the Al-Zn-Mg-Cu-Zr-Sn-RE elements in a mass ratio of 88.5:6.5:2.7:2.1:0.15:0.2:0.3 and dry-blend them in a mixer for 2 hours to produce a premixed powder. A wax-based binder was used, with the components weighed in a mass ratio of paraffin wax: high-density polyethylene: stearic acid: polypropylene = 57:9:11:14. The powder and binder were measured with an accuracy of 0.01 g. The uniformly mixed powder and the prepared binder were weighed to a powder loading of 65 vol.% and mixed in a CF-1L high-pressure internal mixer at 165°C. After 2 hours, the mixture was molten, thoroughly mixed, and then cooled.

[0055] b. Injection Molding: After crushing the feed material, pour it into the barrel of the EM120-SVP / 2 injection molding machine and perform the injection operation. The injection temperature is 160℃, the injection pressure is 175bar, and the mold temperature is 50℃.

[0056] c. Debinding-sintering: trichloroethylene is used for solvent debinding, the dissolution temperature is 45℃, and the dissolution time is 10h; high-purity nitrogen is used as the atmosphere for thermal debinding and sintering, and the thermal debinding heating system is as follows: heating from room temperature to 150℃ at 5℃ / min; heating to 240℃ at 1℃ / min, keeping warm for 120min; heating to 400℃ at 1℃ / min, keeping warm for 180min; heating to 450℃ at 1℃ / min, keeping warm for 120min; heating to 480℃ at a rate of 1℃ / min, keeping warm for 60min; heating to 560℃ at 10℃ / min, keeping warm for 60min; heating to 620℃ at 10℃ / min, keeping warm for 60min; slowly cooling to 200℃ at 2℃ / min and then cooling with the furnace.

[0057] d. Heat treatment: The sintered samples were solution treated in a N2 atmosphere with the following process parameters: heating to 480°C at a rate of 1°C / min and holding for 4 h and 8 h, respectively, followed by water quenching. The solution treated samples were placed in a vacuum drying oven for peak aging treatment with the following process parameters: heating to 120°C at a rate of 5°C / min and holding for 12 h, 24 h, and 48 h, respectively.

[0058] Table 3 Tensile strength of aluminum alloy under different heat treatment systems

[0059]

[0060] Comparing the experimental results in Table 3, it can be seen that after solution-aging heat treatment, the yield strength of the Al-Zn-Mg-Cu-Zr-Sn-RE aluminum alloy is between 457-517 MPa and the tensile strength is between 502-565 MPa. The tensile strength of the injection-molded aluminum alloy prepared by the present invention has reached the level of traditional casting alloys. The optimal heat treatment schedule is 480°C solution treatment for 4 hours followed by 120°C aging for 24 hours. All Al-Zn-Mg-Cu-Zr-Sn-RE aluminum alloys with different rare earth elements achieve the highest mechanical properties under this heat treatment schedule. Among them, the Al-Zn-Mg-Cu-Zr-Sn-Sc aluminum alloy with Sc has the best mechanical properties. This is mainly because Sc has the smallest atomic radius compared to other rare earth elements and the smallest relative difference with Al atomic radius. In the comparative experiment, it has the best effect in improving the overall performance of the aluminum alloy. After heat treatment at 480℃ for 4h and 120℃ for 24h, the yield strength reaches 517MPa and the tensile strength reaches 565MPa.

Claims

1. A method for preparing a high-strength aluminum alloy containing rare earth elements using powder injection molding technology, characterized in that: Through composition design, an Al-Zn-Mg-Cu-Zr-Sn-RE aluminum alloy system was developed to meet the requirements of the injection molding aluminum alloy process. The raw material powders were mixed in a specific proportion, and a wax-based binder suitable for aluminum alloy injection molding was added. The mixture was then mixed on a roller mixer to obtain a feed material. A green body was prepared using injection molding technology. After solvent degreasing, a thermal degreasing and sintering process was performed in a high-purity nitrogen atmosphere. Finally, solution treatment and aging treatment were performed to obtain an injection-molded aluminum alloy product with high mechanical properties. The mass percentages of the alloying elements in the injection molding aluminum alloy are: Zn 4.5-7.5%, Mg 2.0-4.0%, Cu 1.5-3.5%, Sn 0.1-0.4%, RE 0.05-0.4%, Zr 0.025-0.2%, and Al is the balance; RE is Sc, Y or Er; The particle sizes of the raw material powders used for injection molding of aluminum alloys are Al: 10-30 μm, Cu: 10-40 μm, Sn: 5-20 μm, Al-50Zn: 15-45 μm, Al-50Mg: 35-50 μm, and Al-Mg-Zr-RE: 10-30 μm; The degreasing process of the aluminum alloy green body for injection molding is divided into two steps: solvent degreasing and thermal degreasing, wherein the solvent for solvent degreasing is trichloroethylene, the temperature is 40-50°C, and the degreasing time is 9-15 hours; The thermal degreasing and sintering process of the aluminum alloy for injection molding is completed in an integrated manner, and the specific process parameters are: heating from room temperature to 150°C at 5°C / min; heating to 220-250°C at 0.5-2°C / min, keeping warm for 90-180 min; heating to 390-410°C at 0.5-2°C / min, keeping warm for 180-240 min; heating to 440-460°C at 0.5-2°C / min, keeping warm for 120-180 min; heating to 470-480°C at a rate of 0.5-2°C / min, keeping warm for 30-60 min; heating to 550-570°C at 1-10°C / min, keeping warm for 30-60 min; heating to 610-620°C at 1-10°C / min, keeping warm for 60-120 min; heating to 470-480°C at a rate of 0.5-2°C / min, keeping warm for 30-60 min; heating to 550-570°C at 1-10°C / min, keeping warm for 30-60 min; heating to 610-620°C at 1-10°C / min, keeping warm for 60-120 min; heating to 440-460°C at 0.5-2°C / min, keeping warm for 120-180 min; heating to 550-570°C at 1 ℃ / min slowly cooled to 200 ℃ and then cooled in the furnace; Both the thermal debinding process and the sintering process were protected by high-purity nitrogen, with a nitrogen flow rate of 0.1-1 mL / min.

2. The method for preparing a high-strength aluminum alloy containing rare earth elements using powder injection molding technology according to claim 1, characterized in that: The mass percentages of the components of the binder for injection molding aluminum alloy are: paraffin 33-66%, beeswax 0-33%, low-density polyethylene 0-20%, high-density polyethylene 0-20%, polypropylene 0-20% and stearic acid 5-15%.

3. The method for preparing a high-strength aluminum alloy containing rare earth elements using powder injection molding technology according to claim 1, characterized in that: The loading amount of the aluminum alloy feed for injection molding is 58-66 vol.%, that is, the aluminum alloy powder in the feed accounts for 58-66% of the total volume; the mixing parameters are: mixing temperature 160-180 ° C, mixing time is 1.5-2.5 h.

4. The method for preparing a high-strength aluminum alloy containing rare earth elements using powder injection molding technology according to claim 1, wherein: The solution treatment system of the aluminum alloy for injection molding is: heating to 450-480°C at a rate of 1-5°C / min, keeping the temperature for 1-8 hours, and water quenching.

5. The method for preparing a high-strength aluminum alloy containing rare earth elements using powder injection molding technology according to claim 1, characterized in that: The aging treatment system of the aluminum alloy for injection molding is: heating to 120-150°C at a rate of 1-5°C / min, and aging time is 12-48 hours.

Citation Information

Patent Citations

  • A method for preparing high-performance aluminum alloys using powder injection molding technology

    CN107790729B

  • Method for preparing high-performance aluminum alloy by means of powder injection molding technology

    CN107790729A

  • Method for preparing Al-Zn-Mg-Cu series aluminum alloy through powder injection molding technology

    CN114150175A